Structural Optimization of p-GaN Gate GaN-Based High Electron Mobility Transistors - GE Mei; LI Yi; WANG Zhiliang; ZHU Youhua (Nantong Daxue xuebao. Ziran kexue ban)
In order to simplify the complexity of circuit design and reduce the cost, normally-off high electron mobility transistors are more preferable in the industry. The device with p-GaN gate has drawn increasing attention in the industry. In order to improve the threshold voltage and output saturation current of the device, the transfer and output curves are provided by Silvaco TCAD with adjustable thickness of AlGaN barrier layer and Al mole fraction.The thickness of the AlGaN barrier layer is optimized as 20 nm, and the Al mole fraction is optimized as 0.27,resulting in a lager threshold voltage and output saturation current. The band structure of the device and the electron concentration in the AlGaN/GaN channel are simulated to further study the physical mechanism on the relationship between device structure and the performance of the device. The results of the simulation shows that with increase of the thickness of AlGaN barrier layer and Al mole fraction the threshold voltage of the device decreases, while the output saturation current increases. The threshold voltage of the device is related to the band structure when the device is at the off-state, and the output saturation current is related to the electron concentration in the AlGaN/GaN channel when the device is at on-state.